Estudo alelopático, fitoquímico e genotóxico de extratos aquosos de Aspidosperma pyrifolium Mart. e Combretum leprosum Mart. em Allium cepa - Pereira, José Carlos da Silveira (2015)
The Caatinga has great plant diversity, but few native species have phytochemical, allelopathic and genotoxic studies. Aspidosperma pyrifolium and Combretum leprosum are examples of plants of great importance ethnopharmacological that lacking of toxicological studies. The objective was to evaluate the allelopathic influence, cytotoxicity and genotoxicity of aqueous extracts of A. pyrifolium and C. leprosum on germination and early development of commercial seed of Allium cepa (indicator organism) and describing their biochemical profiles. 50 seeds of A. cepa were placed in the presence of aqueous extracts of these plants in concentrations of 200, 400 and 800 mg/L, with four replicates each, the following variables were evaluated: germination, germination speed, length and dry matter of roots, hypocotyl and seedling, seedling biomass density and mitotic index. Qualitative and quantitative tests were performed on various classes of metabolites to describe the biochemical profile. The results of the extracts groups did not differ from negative control group, for the germination characteristics, indicating that the extracts do not have allelopathic effect. However, the mitotic index was identified sublethal cytotoxicity of aqueous extract of C. leprosum, with 200 mg/L. Biochemical profiles identified novel substances for both species. However, due to possible synergistic effects of the extracts more studies are needed to better phytochemical characterization of both species